Reclaiming a Dwelling Place: How a German History Learning Community Handles Traumatic Memories of Shoah Witnesses - Morgan, Katalin Eszter (Forum Pedagogiczne, 2019)
This paper describes the results of an empirical study in which the objective was to find out how traumatic narratives by Shoah survivors are handled in a classroom setting. The study was conducted using an ethnographic approach by means of which a history lesson sequence was observed and analysed. The teaching medium of the lesson was a digitised presentation of memories by Shoah survivors. The description of the lesson establishes how teachers and students negotiate the difficult terrain of an emotional engagement with the testimonies. The findings are discussed by elaborating on the meaning of traumatic memories for the witnesses, and in turn by asking what it means to listen to the telling of such memories. Conclusions are drawn about the overall meaning of (history) education.